REKONSILIASI ANTARA FILSAFAT DAN AGAMA Telaah Pemikiran Filsafat Al-Farabi - Aziza Aryati (JURNAL ILMIAH SYI'AR, 2012)
Al-Farabi is an outstanding Muslim philosopher. He is well known as the second master. He learnt logic, politics, and music. His thought on metaphysics specially emanation has been studied broadly by scholars. Emanation theory that developed by al-Farabi, although regarded inappropriate with cosmonology theory, was an effort to unite religion and philosophy. Trough his thoughts, Al-Farabi, in fact, tried to strengthen the core of Islamic tenet, i.e. tauhid, even though some  scholars denied because of religious reasons.